2009
DOI: 10.1177/0267659109106109
|View full text |Cite
|
Sign up to set email alerts
|

Bivalirudin anticoagulation during cardiac surgery: a single-center experience in 141 patients

Abstract: The feasibility of bivalirudin for anticoagulation during cardiac surgery has been confirmed in four multicenter clinical trials. Here, we report our single-center experience with bivalirudin anticoagulation in "on-pump" and "off-pump" cardiac surgery in a large number of patients with and without heparin antibodies. Data of patients who underwent cardiac surgery with bivalirudin anticoagulation between 06/2003 and 12/2007 at our institution were reviewed. Assessment included procedural success, blood loss, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…There are limited reports describing different ranges of bivalirudin infusion rates during cardiopulmonary bypass, particularly for pediatric patients. 1,2,4,5,79,15 In our experience, the bivalirudin rate was increased as high as 5.0 mg/kg/h for the VAD case while it was decreased to 0.5 mg/kg/h for the BLT case. We questioned whether or not there should be maximum and minimum infusion rates for bivalirudin anticoagulation regardless of the point-of-care ACT values.…”
Section: Discussionmentioning
confidence: 66%
“…There are limited reports describing different ranges of bivalirudin infusion rates during cardiopulmonary bypass, particularly for pediatric patients. 1,2,4,5,79,15 In our experience, the bivalirudin rate was increased as high as 5.0 mg/kg/h for the VAD case while it was decreased to 0.5 mg/kg/h for the BLT case. We questioned whether or not there should be maximum and minimum infusion rates for bivalirudin anticoagulation regardless of the point-of-care ACT values.…”
Section: Discussionmentioning
confidence: 66%
“…Among the DTIs, bivalirudin has the shortest half-life and potentially the best pharmacological profile for use during ECMO, especially given the broad experience with bivalirudin in patients undergoing cardiac surgery and CPB. 36,39 The short half-life of bivalirudin may also be advantageous compared to other DTIs such as argatroban (39-51 minutes) and lepirudin (78 minutes) for titration of anticoagulation. 40,41 Moreover, argatroban and lepirudin may accumulate in hepatic and renal dysfunction, respectively, potentially leading to derangements of anticoagulation target and thus higher incidence of complications.…”
Section: Alternatives To Bivalirudinmentioning
confidence: 99%
“…Bivalirudin binds to both exocite 1 and the active site on thrombin, thus, competing with fibrin for access to exocite 1. [36][37][38][39][40][41] Eighty percent of bivalirudin is eliminated by proteolysis, with the remainder eliminated by renal clearance. The drug has a half-life of 25 minutes.…”
Section: Bivalirudin Pharmacologymentioning
confidence: 99%
“…Prospective studies, such as the randomized controlled EVOLUTION trials in on-pump and off-pump coronary artery bypass grafting (OPCAB) and the CHOOSE trial have established similar safety and efficacy in the use of bivalirudin in comparison to unfractionated heparin. [89][90][91][92] Moreover, , reported that, in "experienced hands", the use of bivalirudin in complex on-pump and off-pump cardiac surgical cases renders good procedural success and minor complications in the areas of perioperative blood loss and transfusion rates. 93 The patient in Case One had a low slope (58 sec/unit/ mL) from the heparin dose response curve.…”
Section: Previous Experience With Bivalirudin During Cardiac Surgerymentioning
confidence: 99%